Etiology and clinical pattern of liver diseases in children - Salih, Maher M.; Ibraheem, Mohammad F.; Nader, Kefah E. (Journal of the Faculty of Medicine Baghdad, 2018)
Background: liver diseases may not be recognized by clinicians, who can lead to a subsequent delay in the initiation of effective therapies, the commonest presenting signs and symptoms of pediatric liver diseases include hepatomegaly, jaundice, coagulopathy or elevation of the liver enzymes or waste products as ammonia. Objectives: To highlight the etiologies, pattern of presentations and the route of diagnosis of all liver diseases in children less than 10 years referred to the Gastroenterology and Hepatology Unit in Children Welfare Teaching Hospital over a six months period. Patients and methods: A prospective study was conducted in the Gastroenterology and Hepatology Unit in the Children Welfare Teaching Hospital / Baghdad Medical City hospital during the period from first of December 2016 to the end of thirty first of May 2017. Forty patients aged below 10 years were thoroughly assessed for possible causes of liver disease and the severity of liver damage. These patients were subjected to a detailed history, thorough physical examination and a list of investigations Results: forty patients their age less than 10 years, the most common age group in this study was from 1 year to 5 years was 17(40%), males are more affected than females in the ratio of 1.5:1, it was found that the mean age of onset is the biliary atresia and Galactosemia cases were within the first week of life, congenital infection cases presented earlier than the two above groups. In this study most of the cases were diagnosed clinically and by available investigations and only cases of biliary atresia and glycogen storage diseases were diagnosed by liver biopsy. Conclusion: All patients presented late with complications, biliary atresia cases were very late in presentation, all with fibrosis. Family history usually very important in hereditary liver diseases as galactosemia and glycogen storage disease a careful physical examination in addition to previous medical history most of the time gives a clue to the final diagnosis.